Urgensi Pendidikan Islam dalam Interaksi Sosial Masyarakat Soppeng: Upaya Mewujudkan Masyarakat Madani - Muh. Arsyad; Bahaking Rama (Madrasah Tsanawiyah DDI Cilellang, 2019)
This research discusses the importance of Islamic education in social interactions in order to realize the civil society in Soppeng Regency. The type of research used is a qualitative descriptive method. The research approach uses theological normative, social, and pedagogical approaches. The informants from this research were the community of the Soppeng Regency, by prioritizing community figures, religious figures, and educational figures. The results of the research found that the relation of social interaction of the people in Soppeng Regency was divided into two, namely: 1) contractual relations in urban communities whose lifestyles began to be influenced by modern lifestyle patterns, and 2) emotional relations based on cultural in rural communities who maintained cultural and traditional lifestyle patterns. The roles of Islamic community figures in the social interaction of the people in Soppeng Regency are founder and manager of Islamic education institutions; as a government partner; providing information on Islamic teaching; give decisions and solutions to community problems. The position of Islamic education in social interaction is very important in order to realize the civil society in Soppeng Regency. This can be seen in the growth of community tolerance, democratic governance that makes events and ceremonies of traditional and religious a work program, even raising the awareness of citizens to resolve their conflicts peacefully on the principle of deliberation based on Islamic teachings fairly without looking at one's social background or stratification.